Contributions of life skills training programs for realizing the rights of children for healthy development - Tefera, Belay (IJRDO - Journal of Social Science and Humanities Research, 2016)
The purpose of this study was to assess the extent to which life skills training programs would assist in meeting children’s right for healthy development by building personal, interpersonal, and social skills ofyoung persons aged 10 to 24 years. A sample of 192 trained young persons were sampled to rate the perceived benefits of the training programs using a five point Likerttype rating scale. Data were also drawn through key informant interviewing of program coordinators and FGD with peer educators. It was found out that there are similarities and variations in the life skills training programs offered to participants across organizations. However, findings indicated that the life skills training programs were rated to make very good (significant) contributions in building the three groups of skills. Although training in social skills appears somehow less emphasized, participants’ ratings indicated that the training had helped improving their social skills as well. This would suggest that there could be a strong skill transfer from one level to another. It is recommended that these findings need to be triangulated with skill performance measures and using a control group for better generalization.